2016
DOI: 10.1002/hec.3430
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting the Level of Health Inequality Aversion in England

Abstract: Health inequality aversion parameters can be used to represent alternative value judgements about policy concern for reducing health inequality versus improving total health. In this study, we use data from an online survey of the general public in England (n = 244) to elicit health inequality aversion parameters for both Atkinson and Kolm social welfare functions. We find median inequality aversion parameters of 10.95 for Atkinson and 0.15 for Kolm. These values suggest substantial concern for health inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 14 publications
0
68
2
Order By: Relevance
“…Research programmes are fortunately progressing in tackling the substantial theoretical and empirical difficulties in quantifying equity and financial impacts in ways suitable for integration in decision-making. [25][26][27] Efficiency and Ethics DPU argue that "[s]ometimes reducing the unfair distribution of health in a population … should be given priority over making a health system more efficient (eg, by pursuing what is most cost-effective to maximize health)" [p1]. 3 This seems eminently reasonable but is actually problematic on grounds of the implied meaning of "efficiency. "…”
Section: The Reference Casementioning
confidence: 99%
“…Research programmes are fortunately progressing in tackling the substantial theoretical and empirical difficulties in quantifying equity and financial impacts in ways suitable for integration in decision-making. [25][26][27] Efficiency and Ethics DPU argue that "[s]ometimes reducing the unfair distribution of health in a population … should be given priority over making a health system more efficient (eg, by pursuing what is most cost-effective to maximize health)" [p1]. 3 This seems eminently reasonable but is actually problematic on grounds of the implied meaning of "efficiency. "…”
Section: The Reference Casementioning
confidence: 99%
“…One strand of this literature in the health field has investigated health inequality aversion, that is, social attitudes towards trade-offs between improving sum total health and reducing socioeconomic inequality in health (Abasolo & Tsuchiya, 2004;Ali, Tsuchiya, Asaria, & Cookson, 2017;Cropper, Krupnick, & Raich, 2016;Dolan & Tsuchiya, 2011;Edlin, Tsuchiya, & Dolan, 2012;Robson, Asaria, Cookson, Tsuchiya, & Ali, 2016), in the context of a wider literature on equity and the economic evaluation of health programs (Baker et al, 2010;Cookson, Griffin, & Nord, 2014;Cookson et al, 2017;Donaldson et al, 2011;Lancsar, Wildman, Donaldson, Ryan, & Baker, 2011). In these studies, health inequality aversion can be quantified using a parameter in a social welfare function.…”
mentioning
confidence: 99%
“…The search strategy was developed in an iterative fashion. First, six "pearls" [22] were identified as starting points, to provide the initial list of key words [6,8,[23][24][25][26]. Second, the MeSH headings associated with these papers were recorded, and a word frequency analysis of the paper titles/ abstracts was undertaken [27].…”
Section: Search Strategymentioning
confidence: 99%
“…Of the 15 studies identified, 8 provided estimates of aversion to inequalities in health between neutrally labelled groups [23,24,31,33,[35][36][37][38], whilst 7 provided estimates of aversion to inequalities in health between socioeconomic groups [6][7][8][9][39][40][41].…”
Section: Choice Contextmentioning
confidence: 99%
See 1 more Smart Citation